2016
DOI: 10.1248/cpb.c16-00083
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Structural Variety of Nonplanar <i>N</i>-Oxyl Radical Catalysts and Their Application to the Aerobic Oxidation of Benzylic C–H Bonds

Abstract: The design and synthesis of structurally variable, nonplanar N-oxyl radical catalysts and their application to the aerobic oxidation, etherification, and acetoamidation of benzylic C-H bonds are described. The catalytic oxidation of C-H bonds represents a powerful tool to synthesize oxygenated functional molecules from simple hydrocarbons in a straightforward way. Electron-deficient N-oxyl radical catalysts, such as phthalimidoyl N-oxyl (PINO) radical, generated from N-hydroxyphthalimide (1), have attracted mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 47 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…NHPI catalysis has always been performed in polar solvents to guarantee the complete solubilization of the polar catalyst, especially at room temperature. As a consequence, the reactivity of this derivative in nonpolar mediums is unknown, and, to date, experimentally undetermined; the huge efforts devoted to the synthesis of more active derivatives seem not to consider such a detrimental aspect …”
Section: Introductionmentioning
confidence: 99%
“…NHPI catalysis has always been performed in polar solvents to guarantee the complete solubilization of the polar catalyst, especially at room temperature. As a consequence, the reactivity of this derivative in nonpolar mediums is unknown, and, to date, experimentally undetermined; the huge efforts devoted to the synthesis of more active derivatives seem not to consider such a detrimental aspect …”
Section: Introductionmentioning
confidence: 99%
“…The presence of a second functionality in the ketone products makes the ketones synthetically much more useful; a number of bioactive molecules can be derived from these products (see Supporting Information, Figure S‐2). As far as we are aware, there appear to be only a few reports on the oxidation of alkylarenes with the alkyl chain functionalized with a nitrile, an acetoxy, or a mesylate moiety, [4d,f,h] and no study is known of those bearing an azide or alkyne group [18] …”
Section: Resultsmentioning
confidence: 99%
“…Whilst these catalytic systems have advanced selective benzylic oxidation considerably, few of them have been demonstrated to tolerate a wide variety of functionalities on the alkyl side chains in benzylic compounds [4] . Notably, the group of Oisaki and Kanai reported a N ‐oxyl radical‐catalyzed benzylic oxidation of side chains bearing various functional groups, [4d] and Sun and co‐workers reported a manganese catalyst that promotes benzylic oxidation of phenethyl acetate (Figure 1b) [4h] . However, no catalytic systems are known of capable of benzylic oxidation of side chains bearing such important functionalities as alkyne, alkene, azide, amino acid, or free amine moieties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the trifluoromethyl group not only strongly stabilizes N , O -acetal functions, and thus renders the formation of the α-trifluoromethyl N -acyliminium ions difficult, but also greatly destabilizes and hinders these ions. A few studies dealing with the addition of nucleophiles on these peculiar species have been reported. ,,, To date, only two studies leading to the functionalization of 5-(trifluoromethyl)-pyrrolidin-2-one derivatives have been described, and none are asymmetric. ,, Fused nitrogen heterocycles carrying the fluorinated group on the bridgehead position were obtained by an intramolecular Friedel–Craft reaction on 5-silyloxy- or 5-hydroxy-5-(trifluoromethyl)-pyrrolidin-2-ones using an excess of a relatively strong Brønsted acid. , The creation of a C–O bond was performed by the addition of methanol in the presence of hydrochloric acid on a α-trifluoromethylated N , F -acetal lactam derivative, because the corresponding N , O -acetal resisted most deoxygenation procedures except for deoxyfluorination . The creation of a tetrasubstituted stereogenic carbon bearing a sterically demanding trifluoromethyl substituent by the addition of a nucleophile on a α-trifluoromethylated N -acyliminium ion is still challenging.…”
Section: Introductionmentioning
confidence: 99%